2009
DOI: 10.1111/j.1365-3156.2008.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based distribution of sulfadoxine‐pyrimethamine for intermittent preventive treatment of malaria during pregnancy improved coverage but reduced antenatal attendance in southern Malawi

Abstract: Summaryobjective To evaluate the impact of a 2-year programme for community-based delivery of sulfadoxine-pyremethamine (SP) on intermittent preventive treatment during pregnancy coverage, antenatal clinic attendance and pregnancy outcome.methods Fourteen intervention and 12 control villages in the catchment areas of Chikwawa and Ngabu Government Hospitals, southern Malawi, were selected. Village-based community health workers were trained in information, education and counselling on malaria control in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 23 publications
(26 reference statements)
0
53
0
Order By: Relevance
“…These included community case management or home management of malaria with or without the use of rapid diagnostic tests [54], distribution of intermittent preventive treatment (IPT) to pregnant women and children [5557] and the promotion of insecticide-impregnated bed nets [58]. …”
Section: Resultsmentioning
confidence: 99%
“…These included community case management or home management of malaria with or without the use of rapid diagnostic tests [54], distribution of intermittent preventive treatment (IPT) to pregnant women and children [5557] and the promotion of insecticide-impregnated bed nets [58]. …”
Section: Resultsmentioning
confidence: 99%
“…Multiple micronutrient supplementation (MMN) among pregnant and lactating women significantly improved hemoglobin, serum ferritin, birth weight, small-for-gestational age (SGA), anemia in children with non-significant impact on serum retinol levels and preterm birth [52][53][54][55][56][57][58][59][60][61] . Malaria prevention in pregnancy showed that the use of ITNs in pregnancy sig- nificantly reduced the risk of peripheral parasitemia [62][63][64][65][66][67] . These findings should be interpreted with caution as limited number of studies were pooled for each intervention due to restricted region and population for inclusion.…”
Section: Findings From the Meta-analysismentioning
confidence: 99%
“…All the studies were conducted in African countries except for three studies, one each from China, India, and Thailand. Interventions were non-integrated in 23 [10,12-14,16-18,20-22,28-33,37,39-42,45,47] of the studies, while in 17 [8,9,19,23-27,34-36,43,44,46,48-50] studies intervention was integrated with routine community-based antenatal care (ANC), primary healthcare (PHC), child health days or measles, and polio campaigns. The primary comparison was between the community-based delivery strategy versus routine or facility-based care.…”
Section: Reviewmentioning
confidence: 99%
“…The integration of CBIs for malaria with existing ANC and immunization campaigns is reportedly more feasible and acceptable, and has reported improved coverage of IPTp to pregnant women [36]. The integration of malaria control programs with such promotional campaigns has resulted in a major increase in treatment coverage and ITNs distribution at a very low cost [23,24,36,43].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation